Economic Structure, Productivity, and Infrastructure Quality in Southern Mexico - Deichmann, Uwe; Fay, Marianne; Koo, Jun; Lall, Somik V. (World Bank, Washington, DC, 2014)
There are large and sustained differences in the economic performance of sub-national regions in most countries. The authors examine the economic structure and productivity in Southern Mexico and compare it with the rest of the country. The authors use firm level data from Mexican manufacturing to test the relative importance of firm level characteristics (such as human capital and technology adoption) compared with external characteristics (such as infrastructure quality and regulatory environment) in explaining productivity differentials. The authors find that the economic structure of Southern Mexico is considerably different from the rest of the country, with the economic landscape dominated by micro enterprises and a relative specialization in low productivity activities. This, coupled with low skill levels and fewer skill upgrading opportunities, reduces the performance of Southern firms. Productivity differentials between Southern firms and others, however, only exist for micro enterprises. The econometric analysis shows that while employee training and technology adoption enhance productivity, access to markets by improving transport infrastructure that link urban areas also have important productivity effects.